Context, comparison, and the other: On Chad Alan Goldberg's Modernity and the Jews in Western Social Thought. (May 2020) - Gerteis, Joseph
Goldberg's Modernity and the Jews in Western Social Thought examines the central place of Jews within foundational social theory in Germany, France, and the United States. In this essay, I provide my take on Goldberg's argument and provide some notes of appreciation for the better purchase it provided me on several authors' positions. I also raise three interrelated points of discussion and critique, related to the relative weight given to the twin themes of modernity and belonging that framed social theorists' understanding of Jews, the question of why it was Jews and not other groups in this central role, and the degree to which comparison to other groups is possible. I argue that giving more central place to the issue of solidarity helps to illuminate the dilemmas Jews were seen to raise, while also highlighting how Goldberg's theoretical framework can help modern theorists to understand the position of other groups.